ANALYSIS OF THE EFFECT OF MINIMUM WAGE, ECONOMIC GROWTH, AND INDUSTRY ON UNEMPLOYMENT IN BANTEN - Muhammad Aditya Darmawan; Kiky Asmara; Fauzatul Laily Nisa (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2026)
PURPOSE - This study aims to analyze the impact of the Regency/City Minimum Wage (UMK), economic growth, and the number of large and medium industries on the unemployment rate in Banten Province.METHODOLOGY - The research employs panel data from eight regencies/cities in Banten Province covering the period 2014–2023. The data were analyzed using multiple linear regression with a Fixed Effect Model estimated through EViews 12.FINDING - The results indicate that the minimum wage and economic growth have a significant negative impact on the unemployment rate, while the number of large and medium industries has a negative but insignificant impact. These findings emphasize the importance of proportional wage policies and inclusive economic growth, as well as the need to optimize the contribution of large and medium industries in supporting job creation in Banten Province.